Damage control of civilian penetrating brain injuries in environments of low neuro-monitoring resources. (3rd March 2016) - Charry, José D.; Rubiano, Andrés M.; Puyana, Juan C.; Carney, Nancy; David Adelson, P.
Abstract: Introduction. Gunshot wounds to the head are more common in military settings. Recently, a damage control (DC) approach for the management of these lesions has been used in combat areas. The aim of this study was to evaluate the results of civilian patients with penetrating gunshot wounds to the head, managed with a strategy of early cranial decompression (ECD) as a DC procedure in a university hospital with few resources for intensive care unit (ICU) neuro-monitoring in Colombia. Materials and methods. Fifty-four patients were operated according to the DC strategy (<12 h after injury), over a 4-year period. Variables were analysed and results were evaluated according to the Glasgow Outcome Scale (GOS) at 12 months post injury; a dichotomous variable was established as 'favourable' (GOS 4–5) or 'unfavourable' (GOS 1–3). A univariate analysis was performed using a χ 2 test. Results. Forty (74.1%) of the patients survived and 36 (90%) of them had favourable GOS. Factors associated with adverse outcomes were: Injury Severity Score (ISS) greater than 25, bi-hemispheric involvement, intra-cerebral haematoma on the first CT, closed basal cisterns and non-reactive pupils in the emergency room. Conclusion. DC for neurotrauma with ECD is an option to improve survival and favourable neurological outcomes 12 months after injury in patients with penetrating traumatic brain injury treated in a university hospital with few resources for ICU neuro-monitoring.